Dynamically Encircling Multiple Exceptional Points in Waveguides System: Asymmetric–symmetric Multimode Switching - Xiaoxiao Wang; Huixin Qi; Yandong Li; Xiaoyong Hu; Xingyuan Wang; Qihuang Gong (Advanced Physics Research)
Abstract Dynamically encircling exceptional points in non‐Hermitian systems leads to counterintuitive chiral mode conversions, which provides a new platform for implementing information processing. Previous research has shown that the position of the starting point determines whether the dynamics are chiral or non‐chiral. Photonic devices that simultaneously realize chiral and non‐chiral mode converters are yet to be investigated. In this letter, a four‐state non‐Hermitian waveguide array with two exceptional points is presented and the dynamical encirclement of each exceptional point and double exceptional points, which possess chiral and non‐chiral dynamics is studied. Encircling a single exceptional point and both exceptional points gives the same outcome but a different encircling process. During non‐chiral dynamics, the initial states are not on the Riemann sheet that forms the EPs, encircling both exceptional points produces more branch cuts than encircling a single exceptional point. An asymmetric–symmetric multimode switch at telecommunication wavelengths is demonstrated. Chiral mode converter and non‐chiral mode converter can be implemented simultaneously on one photonic device. The research enriches the exploration of the physics associated with multiple exceptional points in non‐Hermitian multistate systems and inspires wide applications in on‐chip optical systems.